Verizon acquired Vodafone- Analysis of Market Reaction - Singh, Netra P (Industrija, 2014)
The recent big tickets in telecom industry include Microsoft acquiring part of Nokia for US 7.2 billion, Verizon buy 45% stake in Vodafone for US130 billion, Google acquiring Motorola for 12.5 billion. These buyouts are analyzed and commented by experts of the industry. This research paper is an attempt to analyze and collate their views with respect to Verizon and Vodafone deal. The analysis includes size of the deal, general comments in the media, what is in the deal for Verizon and Vodafone, impact on the eco-system, followed by concluding remarks. In addition, a section of research methodology is also added.